What Skills Do Student Interpreters Need to Learn in Sight Translation Training? - Lee, Jieun (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
Although sight translation is widely taught in interpreter education and practicsed in the field, there has been a dearth of studies on sight translation. This paper presents the preliminary findings of a pilot study comparing six student interpreters and three professional interpreters’ sight translation of an English speech text into Korean, which is their A language. This paper examines their sight translation performances in terms of accuracy, target language expressions and delivery qualities. The results indicate that student interpreters need to further develop their reading skills to accurately understand the source text and distinguish key ideas from ancillary ideas. The data analysis also reveals that student interpreters need to make conscious efforts to distance themselves from the source language form and develop translation skills to avoid literal translations. These findings have pedagogical implications for sight translation training. This paper discusses condensation strategy as an effective method to enhance delivery and target language qualities. Finally, this paper calls for further research on this under-researched component in the interpreting curriculum.